Extracting gravity wave parameters during the September 2002 Southern Hemisphere major sudden stratospheric warming using a SANAE imaging riometer - Mbatha, N.; Sivakumar, V.; Bencherif, H.; Malinga, S. (Annales Geophysicae, 2013)
Using absorption data measured by imaging riometer for ionospheric studies (IRIS) located at the South Africa National Antarctic Expedition (SANAE), Antarctica (72° S, 3° W), we extracted the parameters of gravity waves (GW) of periods between 40 and 50 min during late winter/spring of the year 2002, a period of the unprecedented major sudden stratospheric warming (SSW) in the Southern Hemisphere middle atmosphere. During this period, an unprecedented substantial increase of temperature by about 25–30 K throughout the stratosphere was observed. During the period of the occurrence of the major stratospheric warming, there was a reduction of both the GW horizontal phase speeds and the horizontal wavelengths at 90 km. The GW phase speeds and horizontal wavelengths were observed to reach minimum values of about 7 m s−1 and 19 km, respectively, while during the quiet period the average value of the phase speed and horizontal wavelength was approximately 23 m s−1 and 62 km, respectively. The observed event is discussed in terms of momentum flux and also a potential interaction of gravity waves, planetary waves and mean circulation.